A review of the fossil taxa originally assigned to Pyrrhocoridae (Hemiptera: Heteroptera) - Kment, Petr (Zootaxa, 2021)
The four described fossil taxa originally assigned to Pyrrhocoridae (Hemiptera: Heteroptera) are reviewed. Mesopyrrhocoris fasciatus Hong & Wang, 1990 (correction of gender agreement) from the Lower Cretaceous of Laiyang Basin, Shandong, China, was reclassified as Cimicomorpha incertae sedis by Shcherbakov (2008), an opinion confirmed here. The status of ‘Dysdercus’ cinctus Scudder, 1890 and ‘Dysdercus’ unicolor Scudder, 1890 from the Eocene of Florissant, Colorado, USA, and their placement in Pyrrhocoridae, are doubtful. ‘Pyrrhocoris’ rottensis nom nov. (= Pyrrhocoris tibialis Statz & Wagner, 1950) from the Upper Oligocene of Rott, Germany, is reclassified here as Lygaeoidea incertae sedis due to the presence of ocelli in the fossil. As a result, currently there is no fossil taxon which can be placed in Pyrrhocoroidea with certainty. The extant Pyrrhocoris tibialis Stål, 1874 is confirmed as junior subjective synonym of P. sibiricus Kuschakewitsch, 1866.